Food and Power in the Making: The Double Movement and New Geographies of Food - Maye, Damian (DIE ERDE – Journal of the Geographical Society of Berlin, 2025)
This paper shows how different actors and issues in the food system redefine not just who makes our food but also what food means to us at a societal level, extending earlier frameworks that define food as a commodity, a right, and a common good. The analysis starts by tracing foundational concepts to understand food and power in the making, including patterns of concentration, global food regimes, empire, and corporate power. It then reviews acts of resistance. Polanyi’s double movement is introduced, alongside conventional and alternative food system models and social movements, to interpret resistance. The paper reveals significant power asymmetries and lock-ins and shows how neoliberalism can resist or respond to calls for change and find ways for food as commodity to reassert itself. The final part of the paper considers the land-food-climate nexus, including metabolic food politics, and calls for an additional more-than-human perspective to be developed to interpret these latest geographies of food and power. This new framing is essential because it is not only about who makes and remakes our food, or even our society, but more fundamentally the sustainable future of our planet.